Pengaruh Entrepreneurship Education dan Self-efficacy terhadap Entrepreneurial Intention Mahasiswa - Cahya, Septyan Budy; Rafida, Veni (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the influence of entrepreneurship education and self-efficacy on the Entrepreneurial intention of students in the Business Education Study Program at Universitas Negeri Surabaya. Entrepreneurial intention is considered an important factor in encouraging students to pursue entrepreneurship as a career option and contribute to economic development. Therefore, understanding the factors that shape Entrepreneurial intention is essential for higher education institutions in designing effective entrepreneurship programs. This study employed a quantitative approach using a survey method. The sample consisted of 150 students selected from the Business Education Study Program. Data were collected through a structured questionnaire based on a five-point Likert scale. The collected data were analyzed using multiple linear regression analysis, supported by validity, reliability, normality, multicollinearity, and heteroscedasticity tests to ensure the quality and accuracy of the research findings. The results revealed that entrepreneurship education has a positive and significant effect on students’ entrepreneurial intention. Self-efficacy was also found to have a positive and significant effect on entrepreneurial intention. Furthermore, entrepreneurship education and self-efficacy simultaneously influence students’ entrepreneurial intention. These findings indicate that strengthening entrepreneurship education and enhancing students’ self-confidence are important strategies for fostering Entrepreneurial intention among university students.